The design of a double-tuned two-port surface resonator and its application to in vivo Hydrogen- and Sodium-MRI - Wetterling, Friedrich (Journal of magnetic resonance, 2012)
The design and construction of a two-port surface transceiver resonator for both 1H-and 23Na-MRI in the rodent brain at 7T is described. Double-tuned resonators are required for accurately co-registering multi-nuclei data sets, especially when the time courses of 1H and 23Na signals are of interest as, for instance, when investigating the pathological progression of ischaemic stroke tissue in vivo. In the current study, a single-element two-port surface resonator was developed wherein both frequency components were measured with the same detector element but with each frequency signal routed along different output channels. This was achieved by using the null spot technique, allowing for optimal variable tuning and matching of each channel in situ within the MRI scanner. The 23Na signal to noise ratio, measured in the ventricles of the rat brain, was increased by a factor of four compared to recent state-of-the-art rat brain studies reported in the literature. The resonator’s performance was demonstrated in an in vivo rodent stroke model, where regional variations in 1H apparent diffusion coefficient maps and the 23Na signal were recorded in an interleaved fashion as a function of time in the acute phase of the stroke without having to exchange, re-adjust, or re-connect resonators between scans. Using the practical construction steps described in this paper, this coil design can be easily adapted for MRI of other X-nuclei, such as 17O, 13C, 39K, and 43Ca at various field strengths.
Gesehen am 16.04.2018